Pengaruh Model Hybrid-Problem Based Learning (PBL) terhadap kemampuan berpikir kritis pada mata pelajaran geografi siswa kelas XI SMA Negeri 1 Bangil - Nabila Munsarikha; Dwiyono Hari Utomo; Budijanto Budijanto; Sumarmi Sumarmi (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
This research is motivated by the lack of students' critical thinking skills in geography subjects. Students are only able to understand the theory and concepts but the application of real problems is still limited. The Hybrid-Problem Based Learning (PBL) model provides opportunities for students to actively learn to formulate problems. The type of research used is quasi-experimental with pretest-posttest control group design. Subjects were selected using purposive sampling technique. This study shows the results where the use of the Hybrid-PBL model in geography subjects has an effect on critical thinking skills. This result is evidenced by the results of the Independent Sample T-test which shows the value of sig. (2.tailed) 0.000 less than 0.05. Geography learning activities using Hybrid-PBL are suitable to be applied to help foster critical thinking skills, especially in the step of guiding group investigations because students participate in field observation activities to find relevant information and data to solve problems authentically. While at the initial stage, namely orienting the problem, students did pay close attention to the video, but to formulate problems and hypotheses had a few obstacles where they had not been able to formulate the problem correctly so that in this process needed a little direction from the teacher in order to determine the formulation of the problem and the appropriate hypothesis. The use of media in this stage is expected to be varied properly and appropriately so that students can overcome the difficulties encountered previously. Penelitian ini dilatarbelakangi masih minimnya kemampuan berpikir kritis siswa dalam mata pelajaran geografi. Siswa hanya mampu memahami mengenai teori serta konsep tetapi dalam penerapan masalah nyata masih terbatas. Model Hybrid-Problem Based Learning (PBL) memberi kesempatan bagi siswa supaya belajar aktif untuk merumuskan masalah. Jenis penelitian yang digunakan yaitu quasi experiment dengan pretest-posttest control group design. Subjek dipilih dengan teknik purposive sampling. Penelitian ini menunjukkan hasil dimana penggunaan model Hybrid-PBL pada mata pelajaran geografi memberikan pengaruh terhadap kemampuan berpikir kritis. Hasil ini dibuktikan dari hasil uji Independent Sample T-test yang menunjukkan nilai sig. (2.tailed) 0,000 kurang dari 0,05. Kegiatan pembelajaran geografi menggunakan Hybrid-PBL sesuai diterapkan untuk membantu menumbuhkan kemampuan berpikir kritis terutama pada langkah membimbing penyelidikan secara berkelompok dikarenakan siswa berpartisipasi dalam kegiatan pengamatan di lapangan untuk mencari informasi dan data yang relevan untuk memecahkan permasalahan secara autentik. Sedangkan pada tahapan awal yaitu mengorientasikan pada masalah siswa memang memperhatikan video dengan baik tetapi untuk membuat rumusan masalah dan hipotesis sedikit mengalami hambatan dimana mereka belum mampu merumuskan masalah dengan tepat sehingga pada proses ini membutuhkan sedikit arahan dari guru agar bisa menentukan rumusan masalah dan hipotesis yang sesuai. Penggunaan media dalam tahap ini diharapkan bisa divariasikan dengan baik dan tepat sehingga siswa dapat mengatasi kesulitan yang dihadapi.